The Poisonwood Bible, Lumumba, and A Congo Chronicle: Patrice Lumumba in Urban Art - Vogt, Leonard (Radical Teacher, 2019)
In a course on Art, Politics and Protest, ”the novel and film provide students with an intense introduction to imperialism."